REVIEW: POTENSI DAN ASPEK KEAMANAN BAHAN ALAM LOKAL INDONESIA SEBAGAI ANTI ACNE - Hani Sri Fitriani; Arvenda Rezky Pratama; Laila Musyarrofah; Surya Bin Mirta (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2025)
Acne vulgaris is a complex skin disorder influenced by the colonization of Cutibacterium acnes, increased sebum production, follicular hyperkeratinization, and inflammatory responses. Limitations of conventional therapies, including skin irritation and the emergence of antibiotic resistance, have encouraged the exploration of natural ingredients as alternative anti-acne agents. Indonesia possesses exceptionally high biodiversity, offering significant potential for the development of locally sourced natural anti-acne products. This review discusses the potential and safety aspects of Indonesian local natural ingredients as anti-acne agents based on credible national and international scientific literature. Natural materials such as turmeric (Curcuma longa), Javanese turmeric (Curcuma xanthorrhiza), betel leaf (Piper betle), aloe vera (Aloe vera), gotu kola (Centella asiatica), and green tea (Camellia sinensis) are examined in terms of their biological activities and safety profiles. Emphasis is placed on the importance of raw material standardization, dose control, and evidence-based safety evaluation to support the safe, rational, and competitive utilization of Indonesian local natural ingredients as anti-acne agents. Keywords: acne vulgaris; anti-acne; Cutibacterium acnes; Indonesian local natural ingredients; safety